Investigation of HSA as a biocompatible coating material for arsenic trioxide nanoparticles. Issue 17 (19th April 2018) - Hoonjan, Maneka; Sachdeva, Geetanjali; Chandra, Sudeshna; Kharkar, Prashant S.; Sahu, Niteshkumar; Bhatt, Purvi
Abstract : The synthesis of human serum albumin coated As2 O3 NPs with improved biocompatibility. Abstract : The anticancer properties of arsenic trioxide (As2 O3 ) are accompanied by highly cytotoxic effects on normal cells. This necessitates developing modalities towards the targeted delivery of As2 O3 . Albumins, on account of their large structure and presence of several interacting groups, are ideal for encapsulating or carrying various drugs. In the present study, human serum albumin (HSA) was chosen as a coating agent to increase the biocompatibility of As2 O3 . An in situ chemical precipitation method was adopted for the synthesis of HSA-coated As2 O3 nanoparticles (HSA-As2 O3 NPs) that were further characterized by Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), ultraviolet–visible (UV-vis) spectroscopy, inductively coupled plasma atomic emission spectrometry (ICP-AES), zeta potential and transmission electron microscopy (TEM). HSA-As2 O3 NPs were assessed for their biocompatibility using mouse fibroblast cells (NIH-3T3) and human dermal fibroblast (HDF) cells by a time- and dose-dependent cytocompatibility MTT assay. The safety of the HSA-As2 O3 nanoparticles was assessed using haemolysis and blood cell aggregation studies. Molecular simulation studies provided evidence of interaction between HSA and As2 O3 . Herein, we report the development of a protein-based delivery system for As2 O3 with improved biocompatibility.